Response of Corn and Palmer amaranth to Mesotrione - Alkhraissi, Maha; Chaudhari, Sushila; Jugulam, Mithila (My University, 2018)
Mesotrione is a herbicide used for the selective pre- and post-emergence control of a wide range of broadleaf and grass weeds in corn (Zea mays). It inhibits the enzyme 4-hydroxyphenylpyruvate dioxygenase (HPPD) which leads to stop biosynthesis of plastoquinone, a key factor in the synthesis of carotenoid pigment. The depletion of carotenoids leading to bleaching symptoms followed by necrosis in sensitive plants. Palmer amaranth (Amaranth Palmeri) is one of the major weeds in corn production system. This study was conducted to test the hypothesis that mesotrione may be effective to control Palmer amaranth and safe for use in corn. Therefore, the objective of this research was to evaluate response of corn and Palmer amaranth to mesotrione. Corn and Palmer amaranth plants were treated with mesotrione at 105 g ai ha-1,and plant survival data was collected at 3 week after application. There was no injury reported to any of the corn plant, and plant survival rate was reported 100%. However, Palmer amaranth plants showed bleaching symptoms followed by necrosis and plant death. Only 12.5% Palmer amaranth plants survived after mesotrione application. These results demonstrated the tolerance of corn and sensitivity of Palmer amaranth to mesotrione.
Keywords: Fall 2018